PEMBERDAYAAN FAKIR MISKIN MELALUI PROGRAM KUBE OLEH DINAS SOSIAL DI KECAMATAN TANAHGROGOT KABUPATEN PASER PROVINSI KALIMANTAN TIMUR - Muhammad Hasanurrizqi; Annisa Rahmadanita (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
This research is oriented to the Empowerment of the Poor through the Joint Business Group Program (KUBE) by the Social Service in Tanahgrogot District, Paser Regency, East Kalimantan Province. This study uses qualitative research methods with descriptive analysis methods. This research is based on the Community Empowerment Theory by Mardikanto (2015). This study uses data collection techniques with interviews and observations. The results showed that: the empowerment of the poor through the KUBE Program by the Social Service in Tanahgrogot Subdistrict Paser Regency, East Kalimantan Province was described through 4 (four) main efforts namely: 1) Human Development: KUBE implementation in fostering people or perpetrators from the Social Service and Assistance Agency is to provide information to the Camat and proceed to the village head to look for people who are indeed less capable and have never received assistance. As well as directing the implementation of KUBE to KUBE actors. Empowerment carried out by the Office of Social Affairs has a good impact on the community and its surroundings, that is, it can develop businesses and other skills; 2) Business Development: The development of this business is to provide facilities and infrastructure to support the activities of the KUBE program. Increasing the accessibility of capital and information is the most important thing in this program. The Office of Social Affairs and Assistance also provides services for channeling business results from each group; 3) Community Development: The development of the environment in the implementation of the KUBE program provides an opportunity for the actors to try according to their wishes with an environmentally friendly business and KUBE actors provide employment to the surrounding community so that KUBE actors carry out this program into a positive impact on the surrounding community and the environment beautiful business; 4) Establishing Institutions: This guidance needs to be adjusted to the rules that apply, sometimes it is also in accordance with the agreement of the KUBE perpetrator with the companion. The facilitator assists KUBE actors in solving problems that exist in KUBE actors both internally and externally so that KUBE actors have the momentum in entrepreneurship, the ability to manage groups and individuals, the ability to solve problems in groups. Keywords: empowerment, KUBE program, social service